1999
DOI: 10.1159/000054402
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Release of Anterior Pituitary Hormones: Effect of H<sub>3</sub> Receptor-Mediated Inhibition of Histaminergic Activity or Posterior Hypothalamic Lesion

Abstract: The effect of stress- or lipopolysaccharide (LPS) endotoxin-induced release of ACTH, β-endorphin (β-END) and prolactin (PRL) was investigated in two groups of conscious male rats: (1) Rats pretreated with different H3 receptor agonists, which inhibit neuronal histamine (HA) synthesis and release, and (2) rats with bilateral posterior hypothalamic lesion, which destroys the histaminergic perikarya exclusively localized in the mammillary nuclei. The H3 receptor agonists R(α)methyl-HA, BP 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
(85 reference statements)
2
16
0
Order By: Relevance
“…An intracerebroventricular infusion of histamine increased the level of CRF mRNA in the hypothalamic paraventricular nucleus (Kjaer et al 1998) and the subsequent release of ACTH and corticosterone into plasma (Kjaer et al 1994), suggesting positive regulation of CRF system by histamine. Moreover, stimulation of H3 receptor by R-α-methylhistamine, which is known to reduce the release of endogenous histamine (Ferretti et al 1998), inhibited the ACTH and prolactin responses to restraint stress (Knigge et al 1999). These observations enable us to propose that the putative mechanism of anxiolytic effects of H3 agonists depends on their functional modulation of CRF neurons via inhibition of histamine release.…”
Section: Discussionmentioning
confidence: 81%
“…An intracerebroventricular infusion of histamine increased the level of CRF mRNA in the hypothalamic paraventricular nucleus (Kjaer et al 1998) and the subsequent release of ACTH and corticosterone into plasma (Kjaer et al 1994), suggesting positive regulation of CRF system by histamine. Moreover, stimulation of H3 receptor by R-α-methylhistamine, which is known to reduce the release of endogenous histamine (Ferretti et al 1998), inhibited the ACTH and prolactin responses to restraint stress (Knigge et al 1999). These observations enable us to propose that the putative mechanism of anxiolytic effects of H3 agonists depends on their functional modulation of CRF neurons via inhibition of histamine release.…”
Section: Discussionmentioning
confidence: 81%
“…However, although IME does cross the blood-brain barrier, IME and MEP/CIM may have different sites of action due to the different administration routes (IME ip vs MEP/CIM icv). Since we have previously found similar inhibitory effects on stimulated ACTH secretion of H1 and H2 receptor antagonists administered centrally and of H3 receptor agonists administered systemically (30,32,33), another explanation is more likely. It has been reported that H3 receptors, in addition to their presynaptic localization on histaminergic neurons are also located presynaptically on other aminergic or cholinergic neurons (34)(35)(36).…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, pretreatment with the presynaptic H3 receptor agonist IME inhibited the ACTH response to E and NE. We have previously found that IME as well as other H3 receptor agonists inhibited the ACTH response to different stress stimuli (30), an effect that was prevented by concomitant administration of an H3 receptor antagonist. The difference between the lack of effect of the H1 and H2 receptor antagonists and the inhibitory effect of the H3 receptor agonist is difficult to explain, since similar actions were to be expected.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In agreement they are activated during various forms of stress and heavily project to hypothalamic or limbic brain areas (e.g., amygdala or bed nucleus of the stria terminalis) involved in these responses. Various pharmacological studies have shown the participation of endogenous histamine via H 1 and H 2 receptor stimulation in the adrenocorticotropic hormone (ACTH), corticosterone, prolactin, or renin responses to stressful stimuli like restraint, endotoxin, or dehydration [507,508]. Furthermore, it seems that the activation of various subpopulations of histaminergic neurons within the tuberomammillary nucleus varies according to the nature of stressful stimuli [443,509].…”
Section: Control Of Pituitary Hormone Secretionmentioning
confidence: 99%